Cancer chemopreventive potential of cooked glutinous purple rice on the early stages of hepatocarcinogenesis in rats - Guo, Huina; Punvittayagul, Charatda; Vachiraarunwong, Arpamas; Phannasorn, Warunyoo; Wongpoomchai, Rawiwan (Frontiers in Nutrition, 2022)
Cancer prevention using dietary phytochemicals holds great potential, particularly in the alternative treatment of gastrointestinal tract cancer. Our previous study found that the methanol extract of cooked purple rice performed various biological functions including antioxidant, anti-inflammatory, and antimutagenic activities in in vitro assays. This study aimed to evaluate the chemopreventive effects of cooked glutinous purple rice extract (CRE) obtained from routine rice cooking method on diethylnitrosamine (DEN)-induced hepatic preneoplastic lesions in rats, along with its inhibitory mechanisms. CRE containing γ-oryzanols and high polyphenolic compounds, particularly cyanidin 3-glucoside, was fed to rats over a period 15 weeks. Additionally, injections of triple DEN were administered to rats once a week during the 2nd, 3rd, and 4th weeks of the experiment. The results revealed that CRE did not induce the formation of glutathione S-transferase placental form (GST-P) positive foci as a precancerous lesion during rat hepatocarcinogenesis, indicating non-carcinogenicity. Furthermore, CRE significantly reduced the number and size of GST-P positive foci in DEN-initiated rats. It also modulated microenvironment homeostasis by reducing the number of PCNA positive hepatocytes and by enhancing the number of apoptotic positive hepatocytes in the livers of DEN-initiated rats. Using RT-PCR analysis, CRE decreased the expression of some proinflammatory mediators, including IL-6, IL-1β, iNOS, and COX2, by attenuating the expression of the proliferation marker cyclin E, while also inducing the expression of the apoptotic gene Bax. The inhibitory mechanism at the early stages of hepatocarcinogenesis of CRE may be involved with the suppression of cell proliferation, the enhancement of apoptosis, and the modulation of the proinflammatory system. Anthocyanins, flavonoids, and γ-oryzanol represent a group of promising chemopreventive agents in cooked glutinous purple rice extract. The outcomes of this study can provide an improved understanding of the potential role of the phytochemicals contained in cooked purple glutinous rice with regard to cancer alleviation.